Methodologies on Researches on the Spatiotemporal Dynamics of Plankton in the Chilean Upwelling Zone - Zhou, Guanyi (Transactions on Environment, Energy and Earth Sciences, 2024)
The dynamics of plankton in the Chilean upwelling zone is one of the focal points of current research, with close ties to the study of the marine environment in this region, the economic development of countries along the coast, and the forecasting of the ocean’s effects on global warming. Although some general patterns and driving factors for the plankton dynamics have been identified by researchers, the methods currently in use are diverse and complex, and a universal, efficient, and comprehensive model for simulating the environmental and biological indicators of this sea area has not yet been developed. Consequently, this paper compiles recent research on the dynamics of plankton in the Chilean upwelling area, synthesizes various research methodologies, and conducts a comparative analysis to explore the path toward the development of a universal large-scale model. The study reveals that the main constraints on the development of the aforementioned model are the immaturity of existing models and the limitations of computational power. By refining current models, initiating research on a smaller scale, and collaborating with the field of computer science to enhance computational capabilities, it is anticipated that a new generation of models can be developed, while also providing guidance and assistance for further research on the dynamics of plankton in the Chilean upwelling area.